Economies of writing: revaluations in rhetoric and composition - Horner, Bruce, editor; Nordquist, Brice, editor; Ryan, Susan M., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2017)
Advances scholarship on political economies of writing and writing instruction, considering those economies in terms of course subject, pedagogy, technology, and social practice. Challenges dominant ideologies of writing, writing skills, writing assessment, language, technology, and public rhetoric by revealing the complex and shifting valuations of writing practices.--Provided by publisher.
The politics of valuation in writing assessment / Tony Scott -- (Re)writing economies in a community college: funding, labor, and basic writing / Katie Malcolm -- Dwelling work and the teaching of writing: responding to the pressures of for-profit instruction / Steven Lamos -- Occupying research: again/still / Joan Mullin and Jenn Fishman -- The political economy of English: the capital of literature, creative writing, and composition / James Zebroski -- Economies of knowledge transfer and the use-value of first-year composition / Anis Bawarshi -- Symbolic capital in the first-year composition classroom / Yuching Jill Yang, Kacie Kiser, and Paul Kei Matsuda -- A question of mimetics: graduate student writing courses and the new basic / Kelly Ritter -- Commodifying writing: handbook simplicity versus scholarly complexity / Samantha Looker -- Psychoanalysis, writing pedagogy, and the public: toward a new economy of desire in the classroom and in composition studies / T.R. Johnson -- Literate resources and the contingent value of language / Rebecca Lorimer Leonard -- The rhetoric of economic costs and social benefits in U.S. healthcare language policy / Scott Wible -- Web 2.0 writing as engine of information capital / Billy Pulisevich -- www.english: Internationalized World Wide Web domains and translingual complexities / Jay Jordan -- Habermasochism: the promise of cyberpublics in an information economy / Donna Lecourt -- Tierra contaminada: economies of writing and contaminated ground / Jason Peters -- Democratic rhetoric in the era of neoliberalism / Phyllis Mentzell Ryder -- Afterword: Lessons learned / Deborah Brandt.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Economic aspects; English language -- Rhetoric -- Study and teaching (Higher) -- Political aspects